Bartonella Species in Invasive Rats and Indigenous Rodents from Uganda - Borchert, Jeff N.; Atiku, Linda A.; Mpanga, Joseph T.; Gage, Kenneth L.; Kosoy, Michael Y.; Billeter, Sarah A. (Vector-Borne and Zoonotic Diseases, 2014)
The presence of bartonellae in invasive rats (Rattus rattus) and indigenous rodents (Arvicanthis niloticus and Cricetomys gambianus) from two districts in Uganda, Arua and Zombo, was examined by PCR detection and culture. Blood from a total of 228 R. rattus, 31 A. niloticus, and 5 C. gambianus was screened using genus- specific primers targeting the 16S–23S intergenic spacer region. Furthermore, rodent blood was plated on brain heart infusion blood agar, and isolates were verified as Bartonella species using citrate synthase gene- (gltA) specific primers. One hundred and four fleas recovered from R. rattus were also tested for the presence of Bartonella species using the same gltA primer set. An overall prevalence of 1.3% (three of 228) was obtained in R. rattus, whereas 61.3% of 31 A. niloticus and 60% of five C. gambianus were positive for the presence The presence of bartonellae in invasive rats (Rattus rattus) and indigenous rodents (Arvicanthis niloticus and Cricetomys gambianus) from two districts in Uganda, Arua and Zombo, was examined by PCR detection and culture. Blood from a total of 228 R. rattus, 31 A. niloticus, and 5 C. gambianus was screened using genus-specific primers targeting the 16S–23S intergenic spacer region. Furthermore, rodent blood was plated on brain heart infusion blood agar, and isolates were verified as Bartonella species using citrate synthase gene- (gltA) specific primers. One hundred and four fleas recovered from R. rattus were also tested for the presence of Bartonella species using the same gltA primer set. An overall prevalence of 1.3% (three of 228) was obtained in R. rattus, whereas 61.3% of 31 A. niloticus and 60% of five C. gambianus were positive for the presence of Bartonella species. Genotypes related to Bartonella elizabethae, a known zoonotic pathogen, were detected in three R. rattus and one C. gambianus. Bartonella strains, similar to bacteria detected in indigenous rodents from other African countries, were isolated from the blood of A. niloticus. Bartonellae, similar to bacteria initially cultured from Ornithodorus sonrai (soft tick) from Senegal, were found in two C. gambianus. Interestingly, bartonellae detected in fleas from invasive rats were similar to bacteria identified in indigenous rodents and not their rat hosts, with an overall prevalence of 6.7%. These results suggest that if fleas are competent vectors of these bartonellae, humans residing in these two districts of Uganda are potentially at greater risk for exposure to Bartonella species from native rodents than from invasive rats. The low prevalence of bartonellae in R. rattus was quite surprising, in contrast, to the detection of these organisms in a large percentage of Rattus species from other geographical areas. A possible reason for this disparity is discussed of Bartonella species. Genotypes related to Bartonella elizabethae, a known zoonotic pathogen, were detected in three R. rattus and one C. gambianus. Bartonella strains, similar to bacteria detected in indigenous rodents from other African countries, were isolated from the blood of A. niloticus. Bartonellae, similar to bacteria initially cultured from Ornithodorus sonrai (soft tick) from Senegal, were found in two C. gambianus. Interestingly, bartonellae detected in fleas from invasive rats were similar to bacteria identified in indigenous rodents and not their rat hosts, with an overall prevalence of 6.7%. These results suggest that if fleas are competent vectors of these bartonellae, humans residing in these two districts of Uganda are potentially at greater risk for exposure to Bartonella species from native rodents than from invasive rats. The low prevalence of bartonellae in R. rattus was quite surprising, in contrast, to the detection of these organisms in a large percentage of Rattus species from other geographical areas. A possible reason for this disparity is discussed
Keywords: Bartonella; Rattus rattus; Arvicanthis niloticus; Cricetomys gambianus; Fleas; Uganda